Maximizing the value of systematic reviews in ecology when data or resources are limited. (11th September 2014) - Doerr, Erik D.; Dorrough, Josh; Davies, Micah J.; Doerr, Veronica A. J.; McIntyre, Sue
Abstract Systematic reviews provide a rigorous, repeatable and quantitative method for assessing and synthesizing all available empirical evidence to evaluate a specific research, management, or policy question. They are particularly well suited for evaluating the effectiveness of environmental management actions, and thus for underpinning evidence‐based adaptive natural resource management. However, their current utility may be limited in countries like Australia, where both the amount of research relative to land area and of well‐monitored, active land management for environmental purposes are relatively low. Based on our experience conducting two of the first ecological systematic reviews in Australia, we have developed a number of recommendations for conducting systematic reviews in situations where resources and/or primary research data are limited. We discuss potential modification or augmentation of most aspects of the systematic review process including selection of a review team, question formulation, search strategy, data analysis, and the communication of results, as well as the inherent tradeoffs between systematic thoroughness and available resources that are involved in these changes. We hope that our recommendations will encourage more ecologists to undertake systematic reviews even if primary research and resources to conduct the review appear to be limited, as even a modified systematic review can provide more defensible evidence‐based guidelines for management of natural resources.